The sensible superconductor [magnesium diboride]. - Das, S. R. (IEEE spectrum)
Cheap to make, simple to cool, easy to shape into wires, magnesium diboride could throw the field of superconducting applications wide open. With a superconducting transition temperature of 39 K, it can be conveniently cooled with commercial cryocoolers or liquid hydrogen (boiling point: 20.2 K). A powder that can be found in any well-stocked chemistry laboratory, it had never been tested for superconductivity until very recently. However, just 18 months after its discovery, magnesium diboride is on the road to producing real-world applications. The main properties of the material and the fabrication of superconducting wires are discussed in this article. Its advantages over high-temperature superconductors are discussed